2008
DOI: 10.1002/bip.20856
|View full text |Cite
|
Sign up to set email alerts
|

Use of synthetic signal sequences to explore the protein export machinery

Abstract: The information for correct localization of newly synthesized proteins in both prokaryotes and eukaryotes resides in self‐contained, often transportable targeting sequences. Of these, signal sequences specify that a protein should be secreted from a cell or incorporated into the cytoplasmic membrane. A central puzzle is presented by the lack of primary structural homology among signal sequences, although they share common features in their sequences. Synthetic signal peptides have enabled a wide range of studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 98 publications
1
17
0
Order By: Relevance
“…Because the disulfide bonds of the newly synthesized preprotein can only be formed in the oxidizing environment of periplasm, the mechanism for the translocation of the nascent unfolded polypeptide chain from the translation site in the cytoplasm across the periplasm membrane could be a key determinant for the folding and, consequently, for the expression of the displayed protein on the phage surface (25)(26)(27)(28)(29)(30)(31). Alternative sequences in the signal peptide region have been known to modulate the expression level and folding quality of the displayed protein (25,27,31), but difficulty remains in identifying optimum signal sequences in a vast sequence space for some sc-dsFv constructs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the disulfide bonds of the newly synthesized preprotein can only be formed in the oxidizing environment of periplasm, the mechanism for the translocation of the nascent unfolded polypeptide chain from the translation site in the cytoplasm across the periplasm membrane could be a key determinant for the folding and, consequently, for the expression of the displayed protein on the phage surface (25)(26)(27)(28)(29)(30)(31). Alternative sequences in the signal peptide region have been known to modulate the expression level and folding quality of the displayed protein (25,27,31), but difficulty remains in identifying optimum signal sequences in a vast sequence space for some sc-dsFv constructs.…”
Section: Discussionmentioning
confidence: 99%
“…The key discovery is that the signal sequence variants of the sc-dsFv-pIII fusion protein have varying effects in directing the sc-dsFv expression on the recombinant phage surface. The signal sequence has been known to be responsible for the Sec system-dependent translocation of the pIII fusion protein from the translation site in the cytoplasm to the periplasm membrane (25)(26)(27)(28)(29)(30)(31), a critical process for the integration of the displayed protein on the recombinant phage surface (32). But the optimal signal sequences for the translocation of the pIII fusion protein were not known.…”
mentioning
confidence: 99%
“…The 1999 Nobel Prize in Physiology or Medicine was awarded to Gunter Blobel for the discovery that proteins have intrinsic signals that govern their transport and localization within the cell (Emanuelsson et al 2007;Clérico et al 2008). Indeed, these signal sequences were shown to serve as zipcodes, specifying the eventual destination of the proteins.…”
Section: Chimeras Incorporate Signal Peptidesmentioning
confidence: 99%
“…Signal peptides targeting proteins to the endoplasmic reticulum (ER) membrane in eukaryotes are 15-30 amino acids long, self-contained and removed after targeting (Emanuelsson et al 2007;Clérico et al 2008). In eukaryotes, proteins translocated across the ER membrane are by default transported through the Golgi apparatus and then exported by secretory vesicles (Emanuelsson et al 2007;Clérico et al 2008). Some chimeras incorporate signal peptides that could direct proteins to the ER and Golgi apparatus.…”
Section: Chimeras Incorporate Signal Peptidesmentioning
confidence: 99%
“…23 We found that functional signal sequences were required to have some welldefined properties: an ability of the hydrophobic core to fold as an a-helix, a detergent-like tendency to interact favorably with a membrane, but an inability to stably incorporate into a bilayer as a transmembrane helix. 20,[24][25][26][27][28][29][30][31] In subsequent work, we and others have been able to reconcile how these essential properties allow the secretory machinery to specifically and productively bind and manage signal peptides.…”
Section: 3mentioning
confidence: 99%